METODE ATM (AMATI, TULIS, MODIFIKASI) UNTUK PEMBELAJARAN MENULIS PUISI BERWAWASAN LINGKUNGAN - Wirawan, Abdul Karim (Hasta Wiyata, 2019)
This article contains conceptual ideas about innovative learning methods that can be used for learning to write poetry. This method is an ATM method. The ATM method stands for observing, writing, and modifying. As the name implies, this learning method has three main syntaxes, namely observing, writing, and modifying. Each syntax is translated back into a more specific syntax. This ATM method is implemented in learning to write poetry with environmental insight.